2002
DOI: 10.1007/s004150200062
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic responses during head-up tilt and tilt reversal in two groups with chronic autonomic failure: pure autonomic failure and multiple system atrophy

Abstract: Continuous haemodynamic responses to head-up tilt (HUT) and its reversal were studied in 21 subjects with sympathetic denervation due to primary chronic autonomic failure; 10 had pure autonomic failure (PAF; peripheral failure) and 11 had multiple system atrophy (MSA; central failure); 8 healthy subjects (controls) also were studied. Supine systolic, diastolic and mean arterial pressure (MAP) and total peripheral resistance (TPR) were highest in PAF. The MAP response to HUT and tilt reversal were different bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 32 publications
7
27
1
1
Order By: Relevance
“…1 In these patients, hypertension seems to be related to increased vascular resistance. 38 These patients have low levels of plasma norepinephrine and plasma renin activity, but normal levels of plasma aldosterone, 39 and higher levels of angiotensin II than controls 40 : the latter might play a role in cardiovascular damage in AF.…”
Section: Other Potential Mechanisms Related To Cardiovascular Organ Dmentioning
confidence: 96%
See 1 more Smart Citation
“…1 In these patients, hypertension seems to be related to increased vascular resistance. 38 These patients have low levels of plasma norepinephrine and plasma renin activity, but normal levels of plasma aldosterone, 39 and higher levels of angiotensin II than controls 40 : the latter might play a role in cardiovascular damage in AF.…”
Section: Other Potential Mechanisms Related To Cardiovascular Organ Dmentioning
confidence: 96%
“…1 En estos pacientes, la hipertensión parece estar relacionada con el aumento de la resistencia vascular. 38 Estos pacientes tienen bajos niveles de noradrenalina plasmática y actividad de renina plasmática, pero niveles normales de aldosterona plasmática 39 y niveles más altos de angiotensina II que los controles 40 ; esto último podría desempeñar un papel en la lesión cardiovascular en la INV.…”
Section: Otros Posibles Mecanismos Relacionados Con Lesión Orgánica Cunclassified
“…25,26 Although the BP reaction possibly could be related to amyloid deposition around the peripheral vessels, BP overshoot has been noted in patients with pure autonomic failure without amyloid deposition or other abnormalities perivascularly. 10,11,13 These findings suggest that vascular damages are not directly associated with BP overshoot in FAP.…”
Section: Discussionmentioning
confidence: 74%
“…Attention has also been focused on blood pressure (BP) changes after tilt reversal: patients with autonomic failure show an increase in BP after tilt reversal, as compared with the baseline values before head-up tilt (BP overshoot). 10,11 Thus, post-tilt observations may be particularly useful to evaluate the hemodynamic basis of supine hypertension that often complicates the management of orthostatic hypotension, which is a relatively common complication: Kario et al reported that the incidence of orthostatic hypotension was 9.5% in elderly patients with hypertension. 12 BP overshoot is more pronounced in post-ganglionic disorders (pure autonomic failure) than in pre-ganglionic disorders (multiple system atrophy).…”
Section: Introductionmentioning
confidence: 99%
“…There are no reports specifically about BP overshoot after tilt reversal, except for incidental observations by Chandler and Mathias [1], who noted that mean arterial pressure in the post-tilt period was higher than in the pre-tilt period in PAF patients. However, this study, in a smaller group of MSA and PAF patients, was primarily concerned with the cardiovascular changes during the HUT period rather than the subsequent post-tilt supine period and did not analyse the difference in degree of BP overshoot between patients with PAF and MSA.…”
Section: Discussionmentioning
confidence: 96%